2020
DOI: 10.1080/17496535.2019.1710546
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Decision-Making of Social Welfare Workers in the Transition of Services: The Ethics of Care and Justice Perspectives

Abstract: It is argued that besides the ethic of justice, the ethic of care is essential for social work ethics, and these approaches need to be fused to meet contemporary challenges of New Public Management in public services. The present study explored social welfare workers' ethical decision-making in restructured organisations in Finland. A total of 111 social counsellors and social workers reported a work-related ethical dilemma and its resolution. In ethical decision-making, participants used predominantly justice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Juujärvi et al [17] in their study mentioned the problem of temptation of the care team, the temptation for encountering one's needs and demands, achieving resources or advancing personal benefits through intangible, unethical, unfair or ungrateful behaviors to address internal conflicts and these personal demands would usually cause ethical challenges in the path of clinical decision making. Also, responding to controversial demands of would make them face consequences and they would be forced to choose who to help or whose demand to respond [17]. In line with the present study, Ebrahimi et al [6] concluded that one of the most important ethical conflicts in clinical decision making is to prevent harm to the patient or to the nurse.…”
Section: Discussionmentioning
confidence: 99%
“…Juujärvi et al [17] in their study mentioned the problem of temptation of the care team, the temptation for encountering one's needs and demands, achieving resources or advancing personal benefits through intangible, unethical, unfair or ungrateful behaviors to address internal conflicts and these personal demands would usually cause ethical challenges in the path of clinical decision making. Also, responding to controversial demands of would make them face consequences and they would be forced to choose who to help or whose demand to respond [17]. In line with the present study, Ebrahimi et al [6] concluded that one of the most important ethical conflicts in clinical decision making is to prevent harm to the patient or to the nurse.…”
Section: Discussionmentioning
confidence: 99%
“…Interprofessional learning also develops individual professional identity and ethical thinking. It's based on joint act in the best interests of the clients and challenges unjust or harmful rules (Juujärvi et al 2020;Weinberg & Banks 2019). Members of a single profession may also experience interprofessional collaboration in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…These countries have well‐established professional legacy and professional organizations that enable social workers to be politically active vis‐à‐vis the state. In Finland, Juujärvi, Kallunki, and Luostari (2020) find that social workers acted in the best interests of their clients by challenging unjust or harmful procedures generated by New Public Management (NPM) practices. The authors emphasize existing institutional arrangements in Finland, which are congruent with social work values and strengthen social workers' ability to address ethical conflicts.…”
Section: Thinking About and With The Statementioning
confidence: 99%